FACTORS AFFECTING BOTTLING MACHINES METERING ACCURACY - Elena V. GATILOVA; Alexander G. IVAKHNENKO (Advanced Engineering Research, 2010)
Bottling machines metering accuracy is considered. Key factors affecting bottling machines accuracy are discovered.